Pharmacy services and psychiatric patient satisfaction among community-based health insurance users in Ethiopia - Chanie, Gashaw Sisay; Atalay, Wagaye; Alemayehu, Tekletsadik Tekleslassie; Wube Bayleyegn, Zemenu; Tadesse, Gebresilassie; Fentahun, Setegn; Wassie, Yilkal Abebaw; Tesfaye, Tegenu Chanie; Geremew, Gebremariam Wulie (Frontiers in Medicine, 2024)
Background: The development of community-based health insurance (CBHI) was driven by the need to provide economic protection for the poor against unexpected healthcare expenses. This can lead to increased patient satisfaction with their overall care. Maintaining high levels of client satisfaction with pharmacy services is crucial for effectively treating patients with psychiatric disorders. Therefore, the purpose of this study was to assess the impact of pharmacy services on psychiatry patient satisfaction among users of CBHI in the psychiatric setting. Result: A total of 420 participants were enrolled with a response rate of 99.5%. Overall, 261 (62.1%) of the patients reported being satisfied with the pharmacy service. However, a significant number of patients expressed dissatisfaction with certain aspects of the service, such as pharmacist counseling on medication side effects (43.1%), medication interactions (36.9%), and labeling and dispensing of medicines (42.4%). According to the study, living in an urban area [AOR= 2.0; 95% CI (1.25, 3.2,); P= 0.04], being between the ages of 18-35 and 36-44 [AOR = 2.7, 95% CI (1.38, 5.3), p = 0.04] and AOR = [3.3, 95% CI (1.6, 5.7), p = 0.001] respectively. First and second visits to the institution [AOR= 2.2; 95% CI (1.15, 4.4); P= 0.01] and [AOR= 1.9; 95% CI (1.13, 3.3); P= 0.01] respectively. Having two psychiatric disorders [AOR = 1.8, 95% CI (1.07, 3.07), p = 0.02] and all drug availability [AOR = 1.5, 95% CI (1.3, 3.43), p = 0.02], were positively associated with psychiatry patient pharmacy service satisfaction. Conclusion: In this study, the users of CBHI psychiatric patients were generally satisfied with the pharmacy service. Additionally, being urban residency age (18-44 years), first and second visits to the institution, having two psychiatric disorders and all drug availability were found to have a significant impact on psychiatric patient pharmacy services satisfaction.